A Zn-doped BiOI microsponge-based photocatalyst material for complete photodegradation of environmental contaminants. (22nd September 2021) - Talreja, Neetu; Ashfaq, Mohammad; Chauhan, Divya; Mera, Adriana C.; Rodríguez, C. A.; Mangalaraja, R. V.
Abstract : The present study describes Zn metal incorporation within BiOI microsponge structures for the photocatalytic degradation of tetracycline (TC) antibiotics. Abstract : The present study describes Zn metal incorporation within BiOI microsponge structures for the photocatalytic degradation of tetracycline (TC) antibiotics. Interestingly, Zn metal incorporation increased the band gap value of BiOI. At the same time, the photocatalytic degradation efficiency is increased due to the increment of photodegradation ability and the generation of hydroxyl radicals, and the decrement of the recombination rate. The Zn–BiOI microsponges showed ∼87 and 100% degradation at 10 and 1 mg L −1 of TC concentration, respectively. TC antibiotics degradation was pH-dependent, which increased with the pH of the TC solution. The synthesized Zn–BiOI microsponges were tested against both Gram-negative ( E. coli ) and Gram-positive ( S. aureus ) bacteria and were found to effectively inhibit or kill both bacterial strains. Hence, it is concluded that the synthesized Zn–BiOI microsponges could potentially degrade the TC antibiotics.